2005
DOI: 10.1111/j.1462-5822.2005.00527.x
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy induction favours the generation and maturation of the Coxiella-replicative vacuoles

Abstract: SummaryPathogens evolved mechanisms to invade host cells and to multiply in the cytosol or in compositionally and functionally customized membrane-bound compartments. Coxiella burnetii , the agent of Q fever in man is a Gram-negative g g g g -proteobacterium which multiplies in large, acidified, hydrolase-rich and fusogenic vacuoles with phagolysosomal-like characteristics. We reported previously that C. burnetii phase II replicative compartments are labelled by LC3, a protein specifically localized to autopha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
265
1
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 246 publications
(280 citation statements)
references
References 61 publications
(85 reference statements)
9
265
1
3
Order By: Relevance
“…This has previously led to the conclusion that autophagy is not induced by the bacteria, rather that LC3B-II is not being degraded, however we can show that increasing autophagy through starvation leads to further CCV expansion. Therefore, in support of previously published research [16], we confirm that increased autophagy during infection aids the intracellular success of Coxiella , whether it is actively triggered by the pathogen or not. This is not incompatible with a block in autophagic flux, seen by increased SQSTM1, as the observation that LC3B accumulates inside the CCV gives evidence to believe that the cargo of autophagosomes that fuse with the CCV are not being degraded as readily.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This has previously led to the conclusion that autophagy is not induced by the bacteria, rather that LC3B-II is not being degraded, however we can show that increasing autophagy through starvation leads to further CCV expansion. Therefore, in support of previously published research [16], we confirm that increased autophagy during infection aids the intracellular success of Coxiella , whether it is actively triggered by the pathogen or not. This is not incompatible with a block in autophagic flux, seen by increased SQSTM1, as the observation that LC3B accumulates inside the CCV gives evidence to believe that the cargo of autophagosomes that fuse with the CCV are not being degraded as readily.…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, the autophagy marker MAP1LC3B/LC3B (microtubule associated protein 1 light chain 3 beta) is located inside the CCV, and is recruited there during autophagosome fusion with the CCV [5,13,15]. These fusion events benefit the establishment of the CCV, since induction of autophagy by starvation allows for more infected cells and larger CCVs [16]. LC3B recruitment to the CCV has been shown to be dependent on the Coxiella Dot/Icm effector protein, Cig2 [15].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, we observed the accumulation of endogenous Beclin 1 in the surrounding membrane of the CRV ( Figure 1A). We have previously shown that LC3 also associates with the large CRV; 29 therefore, we next examined whether both Beclin 1 and LC3 were recruited to the same vacuole. Figure 1B clearly shows both endogenous Beclin 1 and GFP-LC3 decorating the large CRV.…”
Section: Resultsmentioning
confidence: 99%
“…times. 29 Moreover, we have shown that Cb invades host cells through a classical phagocytosis involving normal components of the endocytic/phagocytic pathway. In addition, this pathogen actively interacts with autophagosomes to delay the arrival of hydrolytic enzymes facilitating vacuole development.…”
mentioning
confidence: 99%
“…13 Further, the overexpression of this mutant in CHO cells caused a delay in the development of the Coxiella-replicative compartments for up to 24 h after infection. 13,18 We used a GTP-agarose binding assay to study the ability of RAB24 S67L to bind nucleotides. In agreement with the previous reports, we found that the S67L mutant had a reduced ability to bind GTP-agarose as compared to the wild-type protein (Fig.…”
Section: Rab24 Localizes On Inner and Outer Autophagosomal Membranesmentioning
confidence: 99%